Knowledge of Infection Control Among Healthcare Professionals - Liaquat, Maryam; Muhammad Asif,; Khan, Muhammad Atif; Islam, Hira; Shahab Uddin,; Khan, Malika (Indus Journal of Bioscience Research, 2024)
Objective: This study aimed to evaluate the knowledge of infection control practices among healthcare professionals, including surgeons, MBBS doctors, physical therapists, nurses, and dentists, in Karachi, Pakistan. Methods: A descriptive cross-sectional study was conducted among 200 healthcare professionals from public and private facilities. Participants with at least one year of clinical experience were selected using non-probability convenience sampling. A validated Infection Control Standardized Questionnaire assessed knowledge in three domains: hospital-acquired infections, precautionary measures, and hand hygiene protocols. Scores of 7 or above indicated adequate knowledge, while scores below 7 reflected insufficient knowledge. Ethical approval was obtained in accordance with the Declaration of Helsinki. Data were analyzed using SPSS version 25, employing descriptive statistics, chi-square tests, and ANOVA to evaluate associations and differences among professional groups. Results: Of the participants, 52.5% scored 7 or above, demonstrating adequate knowledge, while 47.5% scored below 7. Surgeons had the highest mean knowledge score (7.8 ± 1.2), followed by physical therapists (7.4 ± 1.3), MBBS doctors (6.9 ± 1.4), nurses (6.2 ± 1.5), and dentists (5.8 ± 1.6). Significant differences in knowledge were observed among professions (p < 0.01). Conclusion: Infection control knowledge varied significantly among healthcare professionals, with critical gaps identified among nurses and dentists. Targeted training programs and resource allocation are essential for improving compliance and patient safety.